Optimization problems in designing automobiles - Dyakov, Ivan; Prentkovskis, Olegas (Transport, 2008)
A mathematical model of optimization problems in designing automobiles is suggested and requirements raised are defined taking into account the main technical and economic characteristics of the automobile. The optimality criterion of the integral parts of the automobile is presented. The system approach to the theory of parametric optimization based on generalized models is used and the algorithm for solving the considered problem is offered. First published online: 27 Oct 2010